Bukolinio žanro transformacija Biono kūryboje - Kudulytė-Kairienė, Audronė (Literatūra, 2015)
The article deals with the poetry of the Greek bucolic poet Bion (probably the end of the 2nd century B.C.). Nothing is known about poet’s life except that he was born at Phlossa near Smyrna. The lament Epitaphios Bionos composed by his disciple claims that Bion was poisened, but this story is probably only an invention. The longest and the best preserved of Bion’s poems is the lament Epitaphios Adonis. Seventeen fragments of his other pieces are preserved in Stobaeus, most of them are erotic in tone. Bion was the imitator of Theocritus. All three bucolic poets – Theocritus, Moschus and Bion – wrote in a poetic Doric dialect and used the same metre as well as the same common topics. The peculiar characteristics of Bion poetry and the inherited bucolic elements are discussed. Although his poems are included in the general class of bucolic poetry, the remains show little of the bucolic traces. Bion wrote erotic poetry totally unconnected with the countryside.